THE STATUS OF COMMERCIAL BANKS WORKING WITH INTERNATIONAL LETTERS OF CREDIT - Abdikarimov Ziyodulla A'zamjon o'g'li (Scientific Impulse, 2023)
This article explains what letters of credit are and information about them, as well as what documents are needed to obtain letters of credit. It also shows how banks calculate letters of credit